Evaluation of digital competence level among educators: assessment tools - Elizaveta A. Osipovskaya; Svetlana Yu. Dmitrieva; Anastasiia A. Savelyeva (RUDN Journal of Informatization in Education)
Problem statement. The goal of this study is to conduct a theoretical analysis of the three most commonly used self-reflection tools that evaluate educators' digital competences: SELFIEforSchools, SELFIEforTEACHERS, and the Digital Competence Wheel. The research seeks to address two key questions: 1) what digital competences are crucial for educators in the present day? 2) which assessment tools have been extensively validated for measuring these competences? Methodology . A pilot test was conducted on the Digital Competence Wheel to assess its potential for evaluating digital competences and its potential application in higher education settings. Results . The unprecedented use of technology in education and training as a result of the pandemic COVID-19 has been recorded. This shift to online learning has accelerated and introduced new challenges and changes to educators' roles and skillsets. The growing demand to develop and utilize proper digital competences in the teaching environment has become an essential component of modern higher education systems. Conclusion . Digital competences encompass a combination of knowledge, skills, and attitudes related to the effective use of technology for performing tasks, problem-solving, and secure, creative, independent, and ethical communication. The Digital Competence of Educators framework is one of the two main comprehensive tools specifically designed to support educators, teachers, and trainers.